2001
DOI: 10.1176/appi.ajp.158.9.1400
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-d-Aspartic Acid Receptor Expression in the Dorsolateral Prefrontal Cortex of Elderly Patients With Schizophrenia

Abstract: Objective:The N-methyl-D-aspartic acid (NMDA) class of glutamate receptors has received attention in the pathophysiology of schizophrenia because of the similarity between some schizophrenic symptoms and symptoms caused by NMDA antagonists. To determine if NMDA receptor abnormalities were present at the mRNA level, expression of NMDA receptor (NR) subunits NR 1 , NR 2A , and NR 2B was measured in specimens from the dorsolateral prefrontal cortex and the occipital cortex of elderly patients with schizophrenia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
1
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(113 citation statements)
references
References 94 publications
2
104
1
6
Order By: Relevance
“…Despite accounting for these factors, postmortem studies may find inconsistent results for the same dependent variable. For example, expression of mRNA for the GluN1 subunit of the NMDA glutamate receptor in the frontal cortex in schizophrenia was decreased (Sokolov, 1998), increased (Dracheva et al, 2001; Le Corre et al, 2000), and unchanged (Akbarian et al, 1996) in separate studies using tissues from different brain collections. Such disparate findings may be attributed to differences in methodology, variation in dissection protocols, and differences in the biological substrate due to the heterogeneity of the illness being studied.…”
Section: The Postmortem Substrate: Using Brain Tissues From Subjects mentioning
confidence: 99%
“…Despite accounting for these factors, postmortem studies may find inconsistent results for the same dependent variable. For example, expression of mRNA for the GluN1 subunit of the NMDA glutamate receptor in the frontal cortex in schizophrenia was decreased (Sokolov, 1998), increased (Dracheva et al, 2001; Le Corre et al, 2000), and unchanged (Akbarian et al, 1996) in separate studies using tissues from different brain collections. Such disparate findings may be attributed to differences in methodology, variation in dissection protocols, and differences in the biological substrate due to the heterogeneity of the illness being studied.…”
Section: The Postmortem Substrate: Using Brain Tissues From Subjects mentioning
confidence: 99%
“…35,37 These studies found no changes in transcript expression for NR2A, NR2B and NR2D, a small but significant decrease for NR2C in the frontal cortex in schizophrenia, and identified increased transcript expression for NR2A and PSD-95 in occipital cortex. 35 In addition, these studies reported either increased or unchanged expression of the NR1 transcript, which might be attributed to a difference in the prefrontal cortical area studied (Brodmann area 10 vs 46). For NR2A-D, our present protein data are consistent with previous reports of unaltered expression of these subunits at the transcriptional level.…”
Section: Discussionmentioning
confidence: 97%
“…[31][32][33][34] Changes in the expression of transcripts encoding NMDA receptor subunits in the prefrontal cortex have previously been described in post-mortem schizophrenic brains. [35][36][37] However, relatively little is known about protein expression of these subunits in schizophrenia. Additionally, expression of the NMDA receptor-interacting PSD molecules in schizophrenia have to date only been analyzed on transcriptional level, and primarily in subcortical regions in post-mortem brain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are currently underway to assess NMDA and AMPA receptor subunit mRNA expression in the entorhinal cortex of individuals from the Neuropathology Consortium collection of the Stanley Medical Research Institute as well as a separate cohort. Finally, a number of studies have reported regional and laminar alterations in NMDA and AMPA receptor trafficking proteins in the DLPFC (Beneyto and MeadorWoodruff, 2006;Dracheva et al, 2001;Dracheva et al, 2005), providing insight into additional mechanism of glutamate dysregulation in this region. Due to limitations in resource material, we were unable to assess alterations in the mRNAs encoding glutamate receptor trafficking proteins in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the expression of NMDA and AMPA receptor subunits in the DLPFC and report increased NR1 (Dracheva et al, 2001), NR2D (Akbarian et al, 1996), and GluR1, decreased GluR2 Vawter et al, 2002), and increased (Dracheva et al, 2005) and/or decreased (Beneyto and MeadorWoodruff, 2006) GluR4 subunit mRNA expression in the DLPFC of schizophrenics. Other studies report no change in NMDA receptor mRNA or protein (Kristiansen et al, 2006) or AMPA receptor subunit mRNA (Healy et al, 1998;O'Connor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%